2012
DOI: 10.1016/j.ecocom.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the spatial variability of soil type and tree colonization on the dynamics of Molinia caerulea (L.) Moench in managed heathland

Abstract: European heathland communities on acid, nutrient-poor soils have a high ecological value due to their special environmental conditions. Natural succession (tree colonization and the emergence of grasses) poses a threat to this type of habitat anddifferent types of management strategy must be considered if it is to be maintained. A previous study on a dry heathland area located in the Fontainebleau forest (France) showed a gradual shift from a pure ericaceous standto a mosaic of grasses and Ericaceae, despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Our results did not refute the importance of a possible plant–soil feedback and tended to confirm previous studies that showed that heathlands with thinner O‐horizons had a greater risk of grass invasion (Mobaied et al. ).…”
Section: Discussioncontrasting
confidence: 49%
“…Our results did not refute the importance of a possible plant–soil feedback and tended to confirm previous studies that showed that heathlands with thinner O‐horizons had a greater risk of grass invasion (Mobaied et al. ).…”
Section: Discussioncontrasting
confidence: 49%
“…This maintenance is becoming more and more difficult due to the spatial configuration of the many heathland fragments, which are interspersed within a large matrix of conifer and deciduous forests. The most economical management methods, such as regular mechanical cuttings and woody species removal, are inadequate to maintain specific species in a heathland fragment in the middle of a forest matrix as we showed in previous studies [11,21]. These conditions require additional methods to better preserve this habitat.…”
Section: Introductionmentioning
confidence: 95%
“…Due to edge effects, the estimated values of soil depth at the plot edges might be subject to higher levels of uncertainty than other points within the plot boundaries. Three classes of soil depth were distinguished, in approximated accordance with observed soil horizons in this region [21]: shallow soils (0-20 cm), medium-depth soils (21-40 cm), and deep soils (greater than 40 cm). We used this interpolated map as a soil depth map as shown in Figure 2a.…”
Section: Soil Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the light environment and soil properties can lead to loss or decrease of typical heathland species, (Sørensen & Tybirk ), expansion of grasses (Mobaied et al. ) and changes in the functional composition of the vegetation (Curt et al. ; Mantilla‐Contreras et al.…”
Section: Introductionmentioning
confidence: 99%